(untitled) (Journal of Economic Research & Business Administration, 2019)
This paper discusses patterns of a complex cyclical interaction between phenomena of an economic crisis and creative and innovation activities. Economic growth stimulates investments in innovation that drive creativity and innovation, consequently resulting in further economic growth. However, if there is too much innovation, then this creates challenges in the sense of questioning the established structures, finally creating a need for developing new structures. Organizations, societies, economies or systems can be more or less successful in doing so. As an illustration, the dynamics of the development of creative industries is presented. Based on the conceptions of “creative destruction”, the theory of long economic cycles and its modern modifications, and theory of economic growth based on technological progress, the authors propose and argue a hypothesis-based model of dialectic interrelationship of innovation and economic crisis as a multidimensional (creativity, innovation, economy, time) coiling spiral with a decreasing period over time: creative and innovative activities are provoked and stimulated by a crisis, but, in turn, they are also linked with recurrences of crises. Therefore, a challenge for managers and innovation policy makers lies in defining and supporting a corresponding level of creativity and innovation, that is creativity and innovation optimization.